Rancang Bangun Aplikasi Penilaian Kinerja Karyawan Dengan Metode 360 Derajat Pada PT. E-T-A Indonesia Berbasis Web - Mochtar, Muhammad Denovasto; Tjandrarini, Asteria; Lemantara, Julianto (Jurnal JSIKA, 2014)
PT. E-T-A Indonesia is a branch company of E-T-A GmbH Germany which designs and produces circuit breaker. For ensuring quality according to E-T-A GmbH specification, this company needs to assess itâs employees performance on certain period. Current system requires a lot of efforts, including paperwork and time. This problem makes length of assessment is increase, and moreover the accuracy is decrease. Based on these issues, the application is made to assist the employee performance assessment process with 360 degree method. The application was created by web based. Web was used to provide data availability at the time of the assessment period will take place that will be accessible in an integrated manner. The research results showed that the application of the employee performance appraisal can help PT. E-T-A Indonesia in conduct performance appraisal process. Application performance appraisal can also help PT. E-T-A Indonesia to conduct the assessment process outside the office online.